Investigation on overburden failure and subsurface subsidence characteristics in fully mechanized top-coal caving of “Three-Soft” Thick coal seams - Wenbing Guo; Weiqiang Yang; Zhibo Ge; Bibi Wang; Longxiang Li (Scientific Reports)
Abstract This study investigates overburden deformation and surface subsidence mechanisms in fully mechanized top-coal caving (FMTC) mining of “three-soft” (soft coal seam, soft roof, and soft floor) thick coal seams through physical similarity modeling, addressing aquifer disruption and intense surface responses. The experimental results were validated through field monitoring data, achieving a maximum subsidence discrepancy of 2.9%, which confirmed the model’s reliability. Key findings include: compaction of the mining-induced overburden exhibited distinct stratigraphic heterogeneity, with lower strata exhibited greater fragmentation-induced expansion with bulking coefficients of 1.039, contrasting with upper strata coefficients of 1.003–1.008. However, the high compressibility and low strength of lower soft strata reduced the bulking coefficient compared to conventional geological conditions. Overburden fracture patterns evolved progressively from “simply supported beam” structures during initial failure to “cantilever beam” configurations during periodic weighting. While macroscopic deformation aligned with classical theories, the combined effects of the large 11.3 m mining height and high compressibility in lower soft strata destabilized the overburden structure, accelerating upper strata failure. This increased the water-conducting fracture zone height-to-seam ratio to 12.33, representing a 48.7% enhancement compared to the regional average of 8.29 under similar weak overburden conditions; Surface subsidence basins arose from underground goaf volume expansion driven by high mining height and soft rock compressibility, culminating in a maximum subsidence factor of 0.956, exceeding the empirical value of 0.85 for thick-seam mining by 12.5%. This study elucidates the overburden-surface interaction mechanisms in FMTC mining under “three-soft” conditions, offering actionable theoretical insights for subsidence hazard mitigation.